Duality theory under model uncertainty for non-concave utility functions - Kharytonova, O. O. (Київський національний університет імені Тараса Шевченка, 2019)
The main goal for this paper is to study the robust utility maximization functional,i.e. sup_{X\in\Xi(x)} inf_{Q\in\mathsf{Q}} E_Q [U(X_T)]; of the terminal wealth in complete market models, when the investor is uncertain about the underlying probabilistic model and averse against both risk and model uncertainty. In the previous literature, this problem was studied for strictly concave utility functions and we extended existing results for non-concave utility functions by considering their concavization.Key words: robust utility maximization functional, minimax problem, concavization.Pages of the article in the issue: 50 - 56Language of the article: English